2002
DOI: 10.1103/physrevb.65.054424
|View full text |Cite
|
Sign up to set email alerts
|

Absence of mean-free-path effects in the current-perpendicular-to-plane magnetoresistance of magnetic multilayers

Abstract: The series resistor and Valet-Fert models widely used to describe the current-perpendicular-to-plane ͑CPP͒ magnetoresistances of ferromagnetic/nonmagnetic ͑F/N͒ metal multilayers were recently claimed to be valid only for mean-free paths shorter than layer thicknesses; otherwise the mean-free path was claimed to be an important length scale in the CPP magnetoresistance ͑MR͒. This claim was based on observations of differences in the CPP MR's, after the samples were taken to above their saturation magnetic fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
77
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(79 citation statements)
references
References 29 publications
2
77
0
Order By: Relevance
“…Here ρ is the resistivity of Pt, δ is the spin memory loss parameter 31,32 which describe the spin flip probability when an electron crosses the interface, and R * is an effective interface specific resistance. 7 We found that Equ.…”
Section: Resultsmentioning
confidence: 99%
“…Here ρ is the resistivity of Pt, δ is the spin memory loss parameter 31,32 which describe the spin flip probability when an electron crosses the interface, and R * is an effective interface specific resistance. 7 We found that Equ.…”
Section: Resultsmentioning
confidence: 99%
“…For F/N interfaces, we'll discuss in Section II.B2.b2.b what little is known. Interestingly, inclusion of modest spin-flipping at F/N interfaces does not greatly affect the CPP-MR of simple [F/N] N multilayers [16], where N is a significant number of bilayers. But it does affect the CPP-MR of symmetric exchange-biased spin-valves (EBSVs) [16], made up of only two equal-thickness F-layers, the magnetization of one pinned in a fixed direction by an adjacent antiferromagnet (AF), and the magnetization of the other free to reverse from parallel (P) to antiparallel (AP) to that of the first [17].…”
mentioning
confidence: 99%
“…As explained in [2], we don't trust most of these values. The only one in which we have some trust is our own δ Co/Cu = 0.25 ± 0.1 [4]. But the validity of even this value was unclear [2].…”
mentioning
confidence: 99%
“…Moreover, AΔR for simple [F/N] n multilayers is relatively insensitive to δ F/N . Absent a general technique for measuring δ F/N , values for a few F/N pairs have been inferred [4][5][6][7] from data not optimized for δ F/N . As explained in [2], we don't trust most of these values.…”
mentioning
confidence: 99%
See 1 more Smart Citation